(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
On making a survey of a period of five years in theseschools, It was found that the percentages of children who left school in eachclass, as well as the percentage of children who were promoted fairly constantfrom year to year. On the basis of the actual collection of statistics for theperiod from 1941-42 to 1945-46 and smoothening them to some extent, averagepercentages were worked out both for wastage and stagnation A formula was then devised toascertain the number of students that remain at the end of a given year in eachclass in a system which works under these average conditions. The mathematicalbasis of this formula is given below: “Of those on roll of a class at the “beginning of a year,a certain proportion leaves the school during the year. Let this proportion be‘W’, Of those who remain on roll to the end, a certain proportion passes and ispromoted to the higher standard. Let this proportion be ‘pf . Let the numbersof fresh entrants every year in this class be ‘n’ . If a class if supposed tobe working under these conditions for a sufficiently long period, we Eirerequired to find the number that it will hold on its rolls at a year end. Let‘N’ be the required number. Then a number ‘Np’ passes every year and arepromoted to the higher standard leaving behind ‘N (l-p)’ to repeat in the sameclass. To this is added ‘n’ fresh entrants next year, so that the number onroll at the beginning of the year is N (l – p) + n of these a proportion ‘W’ leaves the school during theyear, leaving behind a proportion “(l-W)” to remain on roll to the end of theyear. Hence (l - W) [ N (l-p) + n] is the number on roll at the end of a year.But this is what we have taken to be ‘N’.